ERADICATION OF CRIMINAL ACTS OF TERRORISM AND PROTECTION OF HUMAN RIGHTS IN INDONESIA - Parlindungan Purba; Rolando Marpaung; Micael Jeriko Damanik; Hendrik Wahyu (Journal of International Islamic Law, Human Right and Public Policy, 2023)
The Law on the Eradication of Terrorism Crime certainly implies the existence of coercive actions by the state against individuals or groups that commit acts of terror in Indonesia. There are allegations of actions that have the potential to violate Human Rights in the process of arrest and detention of individuals suspected of being terrorists. The intended action was allegedly carried out by law enforcement officers, especially in the practice of implementing Article 28 of the Law referred to in terms of regulating arrests and detentions that were not yet in line with respect and protection of human rights. This research is a descriptive analytical study that wants to describe what is legitimate or not a regulatory restriction of human rights, in the paradigm of "Principles of Provisions on the Restriction and Reduction of Human Rights in the International Covenant on Civil and Political Rights" by the state. Therefore, the government must take corrective measures in advance of law enforcement efforts to avoid any alleged human rights violations in the practices of arrest and detention. In addition, efforts to investigate, prosecute and examine the trial must be based on strong reasons in accordance with the existing procedures and oversight mechanisms.